Comparative Analysis Of Digital Or Print Book Reading References Among Journalism Students - Cahyani, Marcella Putri; Wahyunengsih, Wahyunengsih (Universitas Negeri Padang, 2023)
This research is related to the preference for reading printed books with digital books by UIN Jakarta Journalism Study Program students. The purpose of this research is to find out the reading preferences of UIN Jakarta students and find out the advantages and disadvantages of reading printed or physical books. The method used in this research is a quantitative approach method with a descriptive research type, this method uses frequency and percentage variables. This study concludes that UIN Jakarta Journalism Study Program students prefer to read physical books with various advantages of the physical book itself compared to reading digital books which still have shortcomings in quality and convenience for readers